Tariqa and Philanthrophy : The Study of Tariqa Qadiriyah Naqsyabandiyyah Movement in Kuala Tungkal, Jambi - Ulya Fuhaidah (Insaniyat : Journal of Islam and Humanities, 2018)
The emergence of tariqa movements in the Indonesian Archipelago occurred at the same time of the expanding network of ulama who studied at the holy land, Mecca. One of tariqas that has existed as the result of the spreading of such ulama network is the Tariqa Qadiriyah Naqsyabandiyah. This is one of the tariqas that is considered legitimated and followed by thousands of people in Indonesia, including people of Jambi. Yet the development of this tariqa in Jambi, in which its follower has gradually increased since the 1990s, is less exposed. Followers of tariqa have practiced not only religious and ritual gathering, zikr, but also engaged in philanthropic events which risen hundreds of millions of funds. Such philanthropic events had significantly contributed to the tariqa movement from which it is able to stand free from state’s intervention as well as capable to privately fund its educational institution and boarding school. This article intends to seek the historical aspect of the TariqaQadiriyah Naqsyabandiyah and how it contributes in shaping educational institution and economic sphere of people in Jambi. This study therefore uses historical method in perceiving the role of Tariqa in its society.The data for this study were gathered by conducting observation, interview, and document studies.The study concludes that the tariqa movement in Jambi, particularly in Kuala Tungkal, managed to self-fund its boarding school and educational institution which are affiliated with it. The fund is mainly risen from several occasions of commemoration of the tariqa founder, Sheikh Abdul Qadir Jilany.